Design considerations for targeted optical contrast agents - Lee, Jeong Heon; Park, Gwangli; Hong, Gloria H.; Choi, Jungmun; Choi, Hak Soo (Quantitative Imaging in Medicine and Surgery; Vol 2, No 4 (December 24, 2012): Quantitative Imaging in Medicine and Surgery, 2012)
Abstract: Optical fluorescence imaging with the right combination of imaging modality and targeted contrast agents offers tremendous improvement in intraoperative imaging and clinical output (i.e., imageguided cancer surgery). Therefore, it is of paramount importance to gain an in-depth knowledge in the design of targeted contrast agents to meet clinical requirements. Currently, there are several clinically approved contrast agents available; however, none perform optimally in vivo by providing optimum sensitivity, stability, specificity, and safety for target imaging, diagnosis, and therapy. In this review, we discuss basic design considerations for targeted contrast agents in terms of optical and physicochemical properties, biological and physiological interactions, and biodistribution and targeting.